2018
DOI: 10.1016/j.joule.2017.12.007
|View full text |Cite
|
Sign up to set email alerts
|

The Spatial Collection Efficiency of Charge Carriers in Photovoltaic and Photoelectrochemical Cells

Abstract: The spatial collection efficiency portrays the driving forces and loss mechanisms in photovoltaic and photoelectrochemical devices. It is defined as the fraction of photogenerated charge carriers created at a specific point within the device that contribute to the photocurrent. In stratified planar structures, the spatial collection efficiency can be extracted out of photocurrent action spectra measurements empirically, with few a priori assumptions. Although this method was applied to photovoltaic cells made … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
76
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 40 publications
(78 citation statements)
references
References 59 publications
(134 reference statements)
2
76
0
Order By: Relevance
“…The origin of this discrepancy most likely arises from the inability to extract the photogenerated charge carriers due to recombination in thicker films, [30] or the lack of asymmetry for charge transport and collection. [31] In order to reduce these electrical losses, heterogeneously doped hematite photoanodes with the following doping profile were fabricated: 1 cat% Zn -undoped -1 cat% Ti doped. [13] The light and dark current densities of heterogeneously doped hematite photoanodes with hematite thickness of 9 and 14 nm are depicted in Figure S13b (Supporting Information).…”
Section: Ultrathin Optical Aborbersmentioning
confidence: 99%
“…The origin of this discrepancy most likely arises from the inability to extract the photogenerated charge carriers due to recombination in thicker films, [30] or the lack of asymmetry for charge transport and collection. [31] In order to reduce these electrical losses, heterogeneously doped hematite photoanodes with the following doping profile were fabricated: 1 cat% Zn -undoped -1 cat% Ti doped. [13] The light and dark current densities of heterogeneously doped hematite photoanodes with hematite thickness of 9 and 14 nm are depicted in Figure S13b (Supporting Information).…”
Section: Ultrathin Optical Aborbersmentioning
confidence: 99%
“…Evaluating the spatial collection efficiency (SCE), i.e., the yield with which locally photogenerated charge carriers contribute to the photocurrent, has been used to study other types of photovoltaic devices such as crystalline Si, GaAs, CdS/CdTe, CIGS, as well as photoelectrochemical cells . Extending this characterization tool to new device architectures, such as CQD, perovskite, and organic solar cells, remains a challenge due to the complex effect of thin‐film interference, for this effect precludes the use of conventional analytical methods in the calculation of the SCE.…”
mentioning
confidence: 99%
“…Hence, the suggested method has to be refined to accept arbitrary optical generation profiles. Pang et al 5 and Segev et al 9 suggested solving eqn (2) using standard regularization methods, such as Tichonov, 31,32 and applied it to CIGS solar cells 5 and hematite water splitting photoanodes, respectively. 9 In order to apply such methods, eqn (2) must be discretized:…”
Section: Discussionmentioning
confidence: 99%
“…The emergence of such a technique could significantly accelerate device and material development by providing insights into how bulk transport, photocarrier recombination, and surface chemical reaction govern performance characteristics under real operating conditions. In this work, we show that simple experimental techniques can be used to extract the spatial collection efficiency, [3][4][5][6][7][8][9] f(z), thereby allowing different loss mechanisms in an emerging semiconductor photoanode material, g-Cu 3 V 2 O 8 , to be probed and quantified. Defined as the fraction of optically generated charge carriers at a given location that contribute to the chemical reaction, the spatial collection efficiency (SCE) provides a functional depth profile of the active regions in the device.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation